Metabolic signatures from genebank collections: An underexploited resource for human health? - Sreenivasulu, Nese; Alseekh, Saleh; Tiozon, Rhowell N.; Graner, Andreas; Martin, Cathie; Fernie, Alisdair R. (Annual Reviews, 2023)
Despite the almost universal acceptance of the phrase “you are what you eat,” investment in understanding diet-based nutrition to address human health has been dwarfed compared to that for medicine-based interventions. Moreover, traditional breeding has focused on yield to the detriment of nutritional quality, meaning that although caloric content has remained high, the incidence of nutritional deficiencies and accompanying diseases (so-called hidden hunger) has risen dramatically. We review how genome sequencing coupled with metabolomics can facilitate the screening of genebank collections in the search for superior alleles related to the nutritional quality of crops. We argue that the first examples are very promising, suggesting that this approach could benefit broader ranges of crops and compounds with known relevance for human health. We argue that this represents anapproach complementary to metabolic engineering by transgenesis or gene editing that could be used to reverse some of the losses incurred through a recent focus on breeding for yield, although we caution that ensuring such approaches are not (re)introducing antinutrients is also necessary.